The multi-viewing multi-channel multi-polarisation imager – Overview of the 3MI polarimetric mission for aerosol and cloud characterization. (November 2018) - Fougnie, Bertrand; Marbach, Thierry; Lacan, Antoine; Lang, Ruediger; Schlüssel, Peter; Poli, Gabriele; Munro, Rosemary; Couto, André B.
Highlights: Operational spaced-based system for aerosol and cloud determination. Definition of the Multi-view, Multi-spectral and Multi-polarization concept. Characterization of the system, on-ground as well as in-orbit. Ground processing of the Level-1 products. Abstract: The 3MI instrument is one of the missions of the EUMETSAT Polar System Second Generation (EPS-SG) program to be launched in 2021. This polarimetric mission has a direct heritage from the POLDER mission, with improved capabilities and is implemented within a fully operational long-term framework. The spectral range was extended from the visible-near-infrared (410–910 nm) to the shortwave-infrared domain (up to 2200 nm). The spatial resolution (4 km at nadir) and the instantaneous swath (2200 × 2200 km²) were also improved compared to previous POLDER instruments. The 3MI concept of the multi-viewing, multi-spectral and multi-polarized Imaging is described, in particular how these 3 pieces of information are acquired together within a single simple instrument concept. Achieving the performance necessary to meet the mission requirements will rely on a comprehensive initial pre-launch characterization and subsequently extensive in-orbit monitoring based on a vicarious calibration strategy. The level 1 products available to the users will be geo-located Stokes vectors on the native viewing geometry (Level 1B) and geo-projected multi-directional and spectral Stokes vectors (Level 1C). Level-2 products will provide geophysical and microphysical parameters for aerosol and clouds.